Analysis of natural gas vehicle acceptance behavior for Klang Valley, Malaysia. Issue 1 (1st January 2021) - Teoh, Lay Eng; Khoo, Hooi Ling
Abstract: Natural gas vehicles (NGVs) have been regarded as one of the most promising alternatives to tackle the concern on energy dependence and climate change. Despite various efforts in promoting NGVs, the acceptance of NGVs as an alternative fuel vehicle still remains as a challenge to many countries (including Malaysia). As such, an up-to-date and in-depth analysis is certainly required to analyze the market penetration of NGVs especially in the developing countries. In particular for the context of Malaysia, this paper aims to examine the acceptance behavior of private car users on NGVs (in comparison to conventional vehicle) for which the targeted respondents comprises current NGV users as well as non-NGV users. The acceptance behavior analysis also examines numerous aspects in affecting the perceptions of car users on NGV usage. Besides, the intention of NGV users to recommend NGV to the others is investigated. The acceptance behavior analysis is carried out by using discrete choice approach based on the undertaken revealed and stated preference survey. Concisely, the results show that it is promising to boost the NGV usage in Malaysia. The findings revealed that the perceptions of car users towards NGV usage are greatly influenced by numerous factors, namely government policy, market value of NGV, convenience & accessibility, green & technology concern and also the influence of family, friends & colleagues. It is anticipated that the findings are useful to the stakeholders, especially policy makers, in stimulating the usage of NGVs.